PERSEPSI MAHASISWA TERHADAP PELAKSANAAN MAGANG MERDEKA BELAJAR KAMPUS MERDEKA (MBKM) PADA PROGRAM STUDI ILMU ADMINISTRASI NEGARA FAKULTAS ILMU SOSIAL DAN ILMU POLITIK UNIVERSITAS NUSA CENDANA KUPANG - Siti Karisma Ningsih; Hendrik Toda; David W. Rihi (Yayasan Panca Bakti Wiyata Pangandaran, 2025)
The latest model in the education system in higher education is the policy regarding the Merdeka Learning Campus Merdeka (MBKM) program. In implementing the MBKM internship policy, it is necessary to have student perceptions of the implementation of the MBKM internship to see the extent to which the internship can benefit students. The purpose of the study was to analyze and determine student perceptions regarding the implementation of the MBKM internship at the State Administration Science Study Program, Undana Kupang Faculty of Social Sciences. The approach used in the research is descriptive qualitative approach. Data collection methods used in this study are observation, interview and documentation techniques. The results showed that student perceptions in the implementation of MBKM internships as seen from the aspect of involvement have gone well, but there are several obstacles in the process, namely the lack of delivery of debriefing and limited space in one of the processes to support student involvement. In addition, the support of superiors, in this case the PIC, in supporting the internship implementation process is considered insufficient. There are also obstacles in the aspect of work pressure, this can be seen through students' perceptions of work demands that are not relevant to the interests or majors being pursued by students. And also not optimal innovation and physical comfort in the dimension of change and maintenance of systems that refer to management. This can be seen through student perceptions of the discomfort and lack of empowerment felt at the internship site.